1996
DOI: 10.1246/bcsj.69.521
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Behavior of Sulfamethoxazole onto an Alumina-Solution Interface

Abstract: The adsorption measurements of sulfamethoxazole (SM) onto an alumina surface have been done at room temperature with an object to study the mode of SM adsorption at the solution–alumina interface. It is found that the adsorption isotherm is of the Langmuir type, showing a uni-layer formation of the SM molecules on the alumina surface. The adsorption is pH-dependent and found to increase with increasing pH of the medium. The adsorption is quite sensitive to the presence of Cl− and SO42− ions also and shows much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Previous study suggested the interaction between unprotonated surface hydroxyls and SMX is the driving force for SMX sorption. [29] At lower pH ( < 7), there were fewer unprotonated surface hydroxyls, which was in agreement with the lower sorption of AF. Under alkaline condition ( > 7), however, the electrostatic repulsion may decrease the sorption of SMX on AF.…”
Section: Effect Of Solution Phsupporting
confidence: 70%
“…Previous study suggested the interaction between unprotonated surface hydroxyls and SMX is the driving force for SMX sorption. [29] At lower pH ( < 7), there were fewer unprotonated surface hydroxyls, which was in agreement with the lower sorption of AF. Under alkaline condition ( > 7), however, the electrostatic repulsion may decrease the sorption of SMX on AF.…”
Section: Effect Of Solution Phsupporting
confidence: 70%
“…The adsorption was carried out by the contact method as described in our other communications [18][19][20]. In brief, into a 20 ml known solution of K 2 Cr 2 O 7 (245 mg dm −3 ) were added 0.2 g of swollen bio-polymeric beads at constant pH (6.0) and ionic strength (0.001 M KNO 3 ).…”
Section: Adsorption Experimentsmentioning
confidence: 99%
“…The adsorption was carried out by the contact method as described in our other communications 14–16. In brief, firstly the standard nickel sulfate stock solution was prepared by dissolving 0.448 g NiSO 4 ·6H 2 O in 1 L distilled water.…”
Section: Methodsmentioning
confidence: 99%